Understanding the Challenges and Opportunities of Financial Technology to Enabling SMEs Potential - alfiana fitri (Universitas Teknokrat Indonesia, 2020)
The purpose of this study is to describe and interpret the challenges and opportunities of financial technology (fintech) to the development of SMEs. This research tries to capture the interpretation of research subject that is SMEs’ owners, fintech company’s staff as service provider. This research uses descriptive qualitative approach because the data analysis in this research is written or oral and consider the opinion of research resource. Based on the interview to the SME’s owners, we can conclude that they have a good interpretation of fintech, that fintech is something that bring financial services to technology, and that this thing is beneficial for their business development, although not all the SMES owners use this platform. This research also shows that in adopting fintech, SMEs need to consider drivers and barriers that can affect the success of the implementation. This research has identified time, information and skill, concerns over security, legal issues, market needs, the nominal of the transaction and the doubt of the technology to their business practices as the barriers why fintech adoption by SMEs in Gresik Area has still faced any challenges. But in the other hand, there are also opportunities that can be used by SMEs through this platform to expand their business, that is the ease and attractiveness offered by fintech and opportunities to minimize fraud. Finally, the paper recognizes that the support mechanisms for the implementation of fintech within SMEs still has to be increased. Fintech has a future here, SMEs’ owners agreed that fintech is their future. But the rapid development of fintech is increasing the need for financial education. SMEs need full assistance by the regulator to improve their financial literacy to take the most advantage of the financial opportunities made possible by fintech.Kata kunci: fintech; SMEs, opportunities and challenge